SOME CASES OF INTEGRATED SOCIAL SERVICES IN POLAND - Grewiński, Mirosław; Lizut, Jaonna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
In Poland, public operations refer to the European debate on social policy and public policies, which focus on the development of social services and proper public management. An integrated approach to social services is the answer to the need for changes in the attitude to social problems, which require an extensive activity in the public field and the involvement of many organizations and institutions that create networks. This paper presents current experiences in integrating social services in Poland. Mostly, they have a local and testing character, but they are the “starting point” for the reorganization of the social assistance system. The integrated approach emphasizes the need of reorientation in perception of beneficiaries of social assistance, stimulating their activity and targeted public policies so that they take into consideration different lifestyles and needs. The reorganization and management of social policy system should lead to better social service delivery.